Object and Subject Case Marking in Behdini - Toma, Shivan (European Scientific Journal, ESJ, 2018)
Behdini, a variety of Kurdish, is known to be a morphologically rich language demonstrating both subject and object case marking in an unusual typological distribution. This paper reviews differential object marking (DOM) and differential subject marking (DSM) exemplified by a number of allocated languages, and then DOM and DSM are tested whether they apply on Behdini. This study is designed to answer whether Behdini shows DOM or DSM or whether the way Behdini argument structures are encoded in split ergativity completely governs the case marking of objects and subjects in Behdini. Therefore, ergativity in Behdini is tackled in this study. Data to be applied on Behdini in the process of analysing DOM and DSM are inspired from various studies, and my own linguistic knowledge of Behdini is used for the analysis. The results of the study show that the way split ergativity operates in Behdini entirely accounts for object and subject case marking, concluding that Beddini does not demonstrate DOM and DSM.